The Application of Multicultural Education Based on Majapahit Constitution (Kutaramanawa) through the Internet of Things (IoT) - Supriyadi, Aditya Prastian; Pratama, Agus Guna; Sheehan, Muhammad Yusuf Saladin; Riaziz, Muhammad Ardani (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
The Multicultural value has Known and to be part of social life in Nusantara. It has included in Kutaramanawa as Constitution of the Majapahit Kingdom who has made at 1350 Th. The purpose of this research is to implement the multicultural education value of Majapahit Constitution-based Internet of Things (IoT), especially for the student in elementary school. Application Multicultural education value for elementary school students has very important for strengthening tolerance and push peace in the long term. The type of this research is qualitative research. Monitor the technique of data validity using a triangulation technique. Data analysis technique will be used perspective analysis model and interactive. The results of this research show that the Majapahit constitution is some regulation about multicultural values that have enumerated in their social activity life. The multicultural will be a good real example for students, especially if learning methods use the Internet of Things (IoT) through Augmented Reality and Virtual Reality media in order more effective, attractive, and interactive for known of students.